Dynamic Assessment of the Use of Natural Resources in an Agricultural Production Chain - María C. Cortés; Dayhanna S. Vargas; Juan C. Osorio (Modelling and Simulation in Engineering)
Agriculture is fundamental to people’s food sustainability. One of the current challenges is the proper use of resources, mainly nonrenewable resources such as land and water. In this regard, having simulation tools is crucial for assessing how these resources are impacted by agricultural activities and their implications for the long-term development of such economic activities. System dynamics (SD) is a valuable simulation tool that allows the evaluation of complex system behaviours in the long term, so that the possible impact of decision-making can be studied and thus contribute to the development of policies in fields as important as agriculture. One of the main agricultural products in Colombia is the bulb onion, which is an important product for food, and therefore, its cultivation is widespread in some areas of the country, such as the department of Boyacá. In this department, soil degradation and salinization are evident due to the extensive use of natural resources, deforestation, and excessive use of chemical fertilizers, which also affect water quality due to irresponsible land management practices in agricultural areas. This, in turn, impacts crop yield, increases production costs, and leads to further land degradation. That is why a dynamic simulation model is proposed to study the behaviour of soil and water resources in crops; in this case, the model has been applied to the cultivation of bulb onion in Colombia, but it can be easily replicated for other types of crops. The result of the simulation makes it possible to show great impacts on the crop associated with practices such as fertilization plans and irrigation systems that result in valuable resources such as soil and water. It is therefore important to continue evaluating scenarios and involve more resources in the model that allow the definition of policies associated with the sustainable practice of agriculture within a framework of food security and considering the elements of climate change.